2023
DOI: 10.1038/s41598-023-39049-x
|View full text |Cite
|
Sign up to set email alerts
|

The plasma metabolome of long COVID patients two years after infection

Yamilé López-Hernández,
Joel Monárrez-Espino,
David Alejandro García López
et al.

Abstract: One of the major challenges currently faced by global health systems is the prolonged COVID-19 syndrome (also known as “long COVID”) which has emerged as a consequence of the SARS-CoV-2 epidemic. It is estimated that at least 30% of patients who have had COVID-19 will develop long COVID. In this study, our goal was to assess the plasma metabolome in a total of 100 samples collected from healthy controls, COVID-19 patients, and long COVID patients recruited in Mexico between 2020 and 2022. A targeted metabolomi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
3

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 78 publications
3
18
3
Order By: Relevance
“…In our case, no difference between the two studied groups was observed regarding the CAR subclass, and even though a decrease in those LPCs was observed in our study, as shown in Table S3, there were no significant differences in Long COVID vs recovered individuals. Similarly to previous studies, no significant changes were observed in SM in Long COVID patients.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…In our case, no difference between the two studied groups was observed regarding the CAR subclass, and even though a decrease in those LPCs was observed in our study, as shown in Table S3, there were no significant differences in Long COVID vs recovered individuals. Similarly to previous studies, no significant changes were observed in SM in Long COVID patients.…”
Section: Discussionsupporting
confidence: 85%
“…Even though little is known about lipidomic in Long COVID, an increase of CAR levels along with decreased levels of specific LPCs has been previously reported, LPC(16:0), LPC(17:0), LPC(18:0), and LPC (20:4), in Long COVID patients when compared to healthy controls. 6 In our case, no difference between the two studied groups was observed regarding the CAR subclass, and even though a decrease in those LPCs was observed in our study, as shown in Table S3, there were no significant differences in Long COVID vs recovered individuals. Similarly to previous studies, 6 From all the lipid subclasses analyzed, the main one that resulted to be significantly altered in our comparison was ceramides, which were significantly decreased when comparing Long COVID to fully recovered individuals.…”
Section: Lipidomic Profiling Of Long Covid: Implications Of Ceramides...contrasting
confidence: 56%
See 3 more Smart Citations